A future of extreme precipitation and droughts in the Peruvian Andes - Emily R. Potter; Catriona L. Fyffe; Andrew Orr; Duncan J. Quincey; Andrew N. Ross; Sally Rangecroft; Katy Medina; Helen Burns; Alan Llacza; Gerardo Jacome; Robert Å. Hellström; Joshua Castro; et al. (npj Climate and Atmospheric Science, 2023)
Abstract Runoff from glacierised Andean river basins is essential for sustaining the livelihoods of millions of people. By running a high-resolution climate model over the two most glacierised regions of Peru we unravel past climatic trends in precipitation and temperature. Future changes are determined from an ensemble of statistically downscaled global climate models. Projections under the high emissions scenario suggest substantial increases in temperature of 3.6 °C and 4.1 °C in the two regions, accompanied by a 12% precipitation increase by the late 21st century. Crucially, significant increases in precipitation extremes (around 75% for total precipitation on very wet days) occur together with an intensification of meteorological droughts caused by increased evapotranspiration. Despite higher precipitation, glacier mass losses are enhanced under both the highest emission and stabilization emission scenarios. Our modelling provides a new projection of combined and contrasting risks, in a region already experiencing rapid environmental change.